Enriching identity in the "fan nation": the role of social media in the case of a professional sport team - MacIntosh, E.; Abeza, G.; Lee, J. (Sport, Business and Management, 2017)
Purpose: The purpose was to (i) explore how the National Hockey League (NHL) Ottawa Senators` Twitter activity influences (if at all) their followers` activity online, (ii) examine whether followers` Twitter activity level consequently influences their perception of and perceived inclusion within the online central fan group that surrounds the Senators, (iii) assess whether membership can potentially influence followers` enrichment of social identity, and (iv) investigate if fans` identity—and thereby commitment to the team—is impacted by their level of Twitter activity. Design/methodology/approach: The study adopted a case study method focusing on the National Hockey League` (NHL`s) Ottawa Senators, and collected data through a two-phase approach. In the first phase, a focus group was conducted to obtain breadth and depth, as well as to inform and refine the development of questions to be used in the second phase: survey method. In the second phase, a survey was employed to enrich the explanations and attain deeper and broader understanding regarding the research questions. Findings: The results showed that time spent reading and engaging in tweets are predictive of commitment. This study also showed that it is not strictly an individual`s Twitter activity in relation to the Senators (i.e. replying and retweeting) which dictates their membership within the fan group. Rather, it is a person`s activity level with other Senators community members which determines their membership in the team`s fan nation. Findings also suggest that both the evaluative and emotional components of forming a group are lacking within the twitter communication. This only furthers the argument as to why the Senators need to engage in dialogue with their followers. Research limitations/implications: This was a study of one team over several months of only one season and therefore, does not take into account a more long-term oriented strategy to help formulate social identity and team commitment. Originality/value: This study findings informed us that the only predictor that reflected a significant impact on the construction of a Senators fans` social identity was the number of minutes an individual spent reading the team`s tweets per day. However, the study also showed that the expansion of the network with other fans is a critical feature of increasing the fan group identity thus, sport organization's should play a role in helping to foster further engagement with others.